Sugar-sweetened beverages consumption among New Zealand children aged 8-12 years: a cross sectional study of sources and associates/correlates of consumption - Emma Smirk; Hajar Mazahery; Cathryn A. Conlon; Kathryn L. Beck; Cheryl Gammon; Owen Mugridge; Pamela R. von Hurst (BMC, 2021)
Abstract Background The benefit of reducing sugar-sweetened beverage (SSB) consumption is widely accepted, but updated and in-depth data on New Zealand (NZ) children's SSB consumption is lacking. The aims of this study were to describe beverage consumption, focusing on SSBs in primary school age children living in Auckland; to examine the association of selected socio-demographic, home, community and school factors and children's beverage knowledge/attitudes with regards to beverage consumption; to explore the relationship between SSBs consumption and adiposity in children. Methods A cross-sectional, Auckland-wide survey of 578 school age children (8-12 years) was conducted using questionnaires to collect data on beverage consumption, beverage knowledge/attitudes, and selected socio-demographic and home, community, school factors. Body fat percentage (BF%) was assessed using bioelectrical impedance (BIA). Results Ninety-six percent of children consumed ≥1 serving of SSBs a week; with ≥5 servings reported by 62% of children. Of all SSBs assessed, consumption of ≥1 serving of sugar sweetened milk-based beverages (85%, mainly milk drinks made from powder) was most prevalent, followed by fruit juice (46%) and sugar-containing carbonated drinks (39%, mainly soft/fizzy drinks). Among unsweetened beverages, plain water was reported to be consumed < 2 times a day by 22% of children, and plain milk < 1 serving a day by 53%. Higher consumption of SSBs was associated with socio-economic disadvantage, non-NZ European ethnicities (Māori, Pacific, Asian, others), availability of SSBs in the home, frequent takeaway/convenience shop visits, children's incorrect perception of adequate SSBs consumption frequency, and higher BF% (females only). School health policy and encouragement of children to consume un-sweetened beverages was not associated with SSBs consumption. Conclusions The consumption of SSBs is prevalent in NZ school age children, with higher consumption rates observed among those from socially disadvantaged areas. This high consumption is associated with higher BF% in females. Multi-contextual interventions to decrease SSBs should target children, and their families/environment, particularly those from socially disadvantaged areas.